Prevalence of Childhood Unintentional Injuries Presenting to the Emergency Department of a Tertiary Care Hospital: Prevalence of Childhood Unintentional Injuries Presenting to the Emergency Department - Nasr, Mamoona; Hameed, Muhammad Nadeem; Nasir, Hina; Butt, Muhammad Kashif; Hussain, Nayyab (Pakistan Journal of Health Sciences, 2026)
Childhood unintentional injuries are one of the leading public health concerns worldwide. These injuries need immediate medical attention to prevent any adverse outcomes. Objectives: To determine the prevalence, types, severity, and outcome of unintentional injuries in children presenting to the Emergency Department at Shalamar Hospital, Lahore. Methods: This cross-sectional study was conducted at the Department of Pediatrics, Shalamar Hospital, Lahore. Non-probability consecutive sampling was used to include a total of 242 children with unintentional injuries up to 12 years of age. Validated questionnaires filled out by attending doctors, covering demographic details, injury type, injury setting and circumstances, primary caregiver, and clinical outcomes were used to collect the data. SPSS version 25.0 was employed to analyze the data. Results: Out of 242 children, males accounted for 55% of the cases. The mean age of children was 6.5 ± 3.2 years. 35% of the injuries were transport-related injuries, followed by falls, which accounted for 30% of injuries. Minor injuries (40%) were most frequent, followed by moderate (35%) and severe injuries (25%). The average time between injury and hospital presentation was 3.2 ± 1.5 hours. 45% of the children presented within 1st hour of the injury, and 25% presented after 3 hours. There was no significant difference in injury severity by gender. Conclusions: Transport-related injuries and falls are the leading causes of unintentional injuries, which are more common in boys, occurring more frequently among young children.